An evaluation of hospital gown design in relation to female patient's needs and preferences - Vergel De Dios, Rose Lee Arzadon; Mayo, Adelaida Villaraza (2000.)
The study focused on determining whether the design, function and style, of the present hospital gown satisfy the clothing needs and preferences of female patients confined in some hospitals. The study also identified the clothing needs and preferences of the female patients. Consequently, the study provided information on the female patient's clothing needs and preferences in terms of the functional, structural and aethetic aspects of clothing. The survey-evaluation research method was used in the study wherein a number of female patients from various hospitals in Quezon City were purposively selected as respondents. A total of forty-five (45) patients participated in the study. A Likert-type scale questionnaire was distributed to determine their attitude towards the present design of the hospital apparel. Results of the study showed that: 1. In general, female patients feel that with the present design of the hospital gown only fifty-eight point twenty-six percent (58.26%) of their clothing needs is being provided. Whereas, in terms of satisfying their clothing needs, a rating of the respondents regardless of age constituted twenty-six percent (26%). 2. Clothing needs of the female patients include: fabrics that are soft to the body, comfortable clothes that provide ease for movement and ease in putting on and taking the garment off; well fitted clothes that provided generous wraps; light shades of color that exudes a feeling of lightness and accessible placement of garment fastener. 3. Clothing preferences include garment fasteners that do not strangle and are easy to manage such as big plastic buttons and Velcro strips. Also, hospital gowns that have pockets are preferred by a number of the respondents. Although the study had a wide range of participants in terms of age, no significant difference in the results was noted that might invalidate it. Moreover, the difference in the type of hospital gown the respondents used allowed the researcher to compare and analyze the attitude of the two groups involved in the study towards the design of the hospital apparel.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Women's clothing